3D printing personalized guide plate in the management of recurrent intramuscular venous malformations: A single center experience. (June 2023) - Han, Tao; Jiang, Shupei; Xiong, Jiageng; Cui, Jie; Shen, Weimin
Objective: This study aimed to investigate the feasibility and effectiveness of 3D printing personalized guide plate in the management of recurrent intramuscular venous malformations (IVM). Methods: Fifteen patients with recurrent IVM were retrospectively assessed. 3D-slicer software was used to extract and reconstruct the imaging data from CT and/or MRI to highlight the morphology, size, and puncture depth of the lesion. With the guidance of personalized plate, complete excision of the IVM was adopted along the pre-marked (methylene blue, MB) margin. Results: Personalized guide plate matched involved extremity well, and MB-puncture approach was consistent with preoperative design. All IVMs were removed radically in one single session. Complete pain relief was obtained in all cases postoperatively. Conclusion: The application of 3D printing guide plate can be safe, effective, and reliable to confirming the precise margin of IVM, renders a promising technique with a high practical value in resection of recurrent lesion.